Analisis Pemanfaatan Wifi Melalui Taman Baca Digital sebagai Alat Komunikasi dalam Meningkatkan literasi Baca Nagari Pasilihan - Tri Yuliani; Deswita; Riki Rikarno; Aini Ahmad, Mutia (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study aims to analyze the utilization of WiFi through the Digital Reading Park as a communication tool to enhance reading literacy in Nagari Pasilihan. In an era where digital access is increasingly crucial for education and community empowerment, the presence of free WiFi infrastructure in public spaces opens new opportunities for literacy development in rural areas. The research adopts a qualitative descriptive method, combining field observations, interviews with community members, local leaders, and youth, as well as document analysis. The findings reveal that the Digital Reading Park, supported by accessible internet, serves not only as a center for reading and learning but also as a medium for social communication and knowledge sharing. It significantly increases reading interest among the youth, fosters digital literacy, and strengthens community engagement. However, challenges such as limited digital content in local languages and lack of consistent facilitation remain. The study concludes that the integration of digital infrastructure with community-based reading spaces can play a transformative role in improving literacy levels, especially when aligned with local cultural values and participatory management. It highlights the importance of collaboration between government, community, and educational stakeholders to ensure sustainability and inclusivity. This research contributes to the growing discourse on digital inclusion and grassroots communication strategies for literacy improvement in marginalized rural communities.